Designing a module for learning plant biodiversity: An effort for conservation of local wisdom - Kistantia Elok Mumpuni; Herawati Susilo; Fatchur Rohman; Murni Ramli (Biosfer: Jurnal Pendidikan Biologi, 2022)
This research aims to develop a module based on plant biodiversity and conservation in the Kudus area for high school students. The R&D research design, according to Borg & Gall, was implemented. The module was developed in five stages: research and information-gathering, planning; initial product development; preliminary field test; and product revision. Assessment and review of the module were performed by seven expert validators. Validity and reliability of the assessment instrument for the module were conducted and participated by 68 students. Thirty-one students became participants in the field test. Data were collected using a validation sheet and questionnaire. Data Analysis utilized excel, SPSS, and Rasch. Based on the assessment of validator experts, the module was declared valid. The module validation test gained an average score of 3.68 (very good). Students' responses showed that the Person measure was +3.22 logit, indicating that the students tended to agree with the proposed questions. The person and item reliability were 0.84 and 0.77, respectively. These values mean that the person reliability showed high consistency. The result of Rasch Analysis clarified the acceptance of students regarding the module both from Kudus and Non Kudus area. The results also showed students' interest and understanding of the issue of conservation and biodiversity, as well as their awareness of the local wisdom. It is recommended to develop a similar module as an effort of local potencies conservation.